The thermodynamics and kinetics of electron transfer in the cytochrome P450cam enzyme system. - Honeychurch, M; Hill, A; Wong, L (1999)
In anaerobic environments the first electron transfer in substrate-free P450cam is known to be thermodynamically unfavourable, but in the presence of dioxygen the reduction potential for the reaction shifts positively to make electron transfer thermodynamically favourable. Nevertheless a slower rate of electron transfer is observed in the substrate-free P450cam compared to substrate-bound P450cam. The ferric haem centre in substrate-free P450cam changes from six co-ordinate to five co-ordinate when reduced whereas in substrate-bound P450cam the iron centre remains five co-ordinate in both oxidation states. The slower rate of electron transfer in the substrate-free P450cam is therefore attributed to a larger reorganisation energy as predicted by Marcus theory.